Etude de Fiabilité et Sureté de Fonctionnement des Composants Electroniques - Hamdi Achtar (My University, 2015)
The reliability of electronic components for automobile traction is a sensitive point of their development and therefore the technological growth of electric vehicles. Due to their mode operate and their environment, these components are subjected to higher stress especially in conventional industrial applications. It is therefore important to know these constraints if we want to estimate their life and thus the reliability of the entire system. In the case of a reliability study, based on the thermal fatigue problems, it is important to estimate the temperature called "fragile zones" of the component. A one-dimensional and three-dimensional analysis of TLM was made to study the self heating effect in the IGBT devices. The results clearly confirm that the IGBT modules are capable of generating a considerable amount of heat which must be dissipated effectively to avoid the influence on the component's operation and even its lifetime. The evaluation of the reliability of a power module is determined from the reliabilities of its components interconnected in series and in parallel, but we needed basic collections of all the specific parameters of the inserted components (Diodes and Transistors ) to determine the rate of probable failure and estimate their lifetime. The results show that the IGBT failure rate increases for an increase or rise in junction temperature, thus indicating that the components in continuous thermal stresses and along periods (several years) failure due to the semiconductor junction strains , so the power module will be no in normal operation and we will have an anomaly of the application system.